Establishment of a novel rat model without blood priming during normothermic cardiopulmonary bypass. (January 2014) - Zhu, X; Ji, B; Liu, J; Sun, Y; Wu, S; Zheng, Z; Long, C; Tang, Y
Objective: An effective animal model was needed for research on the pathophysiology of cardiopulmonary bypass (CPB). Rat models were considered suitable for research into CPB, recently. The aim of the article is to establish a simple and safe CPB model without blood priming in rats, containing the advantages of controlling temperature precisely, being similar to the clinical process and laying the foundation for the further study of a deep hypothermic circulatory arrest (DHCA) model. Materials and Methods: Ten Sprague-Dawley rats, divided into a CPB group (n=7) and a sham group (n=3), received sevoflurane inhalation anesthesia and were maintained in an anesthesia state by intubation. The entire CPB circuit consisted of a reservoir, a membrane oxygenator, a roller pump, a heat exchanger and a heat cooler, all of which were connected via silicon tubes. The volume of the priming solution, composed of 6% HES130/0.4 and 125 IU heparin, was less than 12 ml. In the CPB group, a 22G catheter was placed in the left femoral artery for monitoring arterial blood pressure, a 20G catheter was placed in a tail artery for arterial inflow and a homemade, multiorificed catheter was inserted into a right jugular vein for venous drainage. After 90 minutes, the CPB process was terminated when vital signs were stable. In the sham group, the same surgical process was conducted except for the venous drainage. Post-oxygenator blood gas and hemodynamic parameters were measured at each time point before CPB, during CPB and after CPB. Results: All CPB processes were successfully achieved. Blood gas analysis and hemodynamic parameters of each time point were in accordance with normal ranges. The vital signs of all rats were stable. Conclusion: The establishment of CPB without blood priming in rats can be achieved successfully. The rat model could be used to study short-term or long-term organ injury mechanisms caused by CPB. Furthermore, on the basis of the precise control of temperature and the depth of anesthesia, the DHCA model in rats could be developed further to study pathophysiological changes of neurological and other organ functions in the future.